Investigation of Embryotoxic Interaction between Insecticide Pirimor 50 WG and Fungicide Score 250 EC on Chicken Embryos - Major, László; Szabó, Friderika; Petes, Szabolcs; Buda, István; Saidon, Nadhirah Binti; Lehel, József (GEORGIKON FOR AGRICULTURE, 2024)
The aim of this study was to investigate the single and combined embryotoxic effects of Pirimor 50 WG insecticide (500 g/kg pirimicarb) and Score 250 EC fungicide (250 g/l difenoconazole) on the development of chicken embryos. The test materials were injected in 0.1 ml volume into the air chamber of the chicken eggs on the first day of the incubation and the embryos were examined on day 18 of the incubation. During the necropsy the followings were recorded: body weight, embryonic mortality and the type of developmental anomalies. Based on the results of the experiment, embryonic mortality increased in all treated groups compared to the control. Developmental anomalies were not recorded in the individually treated groups, while abnormalities occur in only one embryo in the combination treatment group. The average body weight of the embryos in the treated groups was lower than that of the control group, but the difference was only significant as a result of the combined treatment. The combined administration of the test materials increased the embryotoxicity compared to the individual toxicity tests that was presumably manifested as an additive toxic interaction.
Keywords: interaction; embryotoxicity; chicken embryo; pirimicarb; difenoconazole